Phenomenology of religion - Barua, Archana (Lexington Books, 2009)
What is phenomenology? -- What is phenomenology of religion? -- The structure of religious experience -- Deciphering the signs of the sacred: -- A phenomenological approach to religious world -- Religious meaning